Effectiveness of E-Puber Application (Empowered Women) with A Health Belief Approach to Eudaimonic Well-Being of Menopausal Women - Munawaroh, Siti; Listiana, Eka; Mubarak, Zaky; Trilestasri, Heni (Indonesian Journal of Global Health Research, 2024)
Menopause is not a disease, but a condition that affects women's lives. Menopause is a physiological thing for women because of changes in estrogen hormones. Changes in estrogen hormones that occur make menopausal women easily anxious, have difficulty sleeping, dyspareunia, lose self-confidence, or eudaimonic well being. This condition will affect the quality of life in menopausal women. This study aims to determine the effectiveness of the E-Puber Application (Empowered Women) with a Health Belief Approach to the Eudaimonic Well Being of Menopausal Women. The design of this study used quasi-experiment with control group involving 100 samples of menopausal women. Sample selection was carried out using a simple random sampling technique and using the Eudaimonic Well Being Questionnaire (QEWB) and data analysis was carried out using an independent t-test. The results of the study showed that the p value = 0.008 (p value <0.05) which means that there was a significant difference in the Eudaimonic Well Being variable after getting the E-Puber application. The E-Puber application with a Health Belief approach is used as an effort to prevent psychological problems experienced by menopausal women, in the form of digitalization so that it can improve Eudaimonic Well Being and increase existing potential.